Embryonic piRNAs target horizontally transferred vertebrate transposons in assassin bugs - Brito, Tarcísio Fontenele de; Arruda Cardoso, Maira; Atinbayeva, Nazerke; Alexandre de Abreu Brito, Ingrid; Amaro da Costa, Lucas; Iovino, Nicola; Pane, Attilio (Frontiers in Cell and Developmental Biology, 2024)
IntroductionPiwi proteins and the associated Piwi-interacting RNAs (piRNAs) coordinate a surveillance system that protects the animal genome from DNA damage induced by transposable element (TE) mobilization. While the pathway has been described in detail in the fruit fly Drosophila melanogaster, much less is known in more basal insects. Rhodnius prolixus is an hemipteran insect and one of the major vectors of Chagas disease. Rhodnius acquired specific classes of horizontally transferred transposons (HTTs) by feeding on bats, opossums and squirrel monkeys, thus providing the opportunity to investigate the piRNA-base response against HTTs in this species.MethodsSmallRNA-Seq reads mapping to HTTs and resident transposable elements were quantified and checked for piRNA features like 1U a 10A biases, ping-pong and phasing signatures. Uniquely mapped piRNAs were used to identify piRNA clusters in Rhodnius’ genome. RNA-Seq data was used to quantify transposon and Rp-PIWI genes expression levels and were validated by qRT-PCR.ResultsBy analyzing the temporal dynamics of piRNA cluster expression and piRNA production during critical stages of Rhodnius development, we show that peak levels of ∼28 nt long piRNAs correlate with reduced HTT and resident TE expression primarily during embryogenesis. Strikingly, while resident TEs piRNAs seem to engage in a typical ping-pong amplification mechanism, sense and antisense HTT piRNAs instead overlap by ∼20 nt or do not display ping-pong signatures.DiscussionOur data shed light on the biogenesis and functions of the piRNAs in Rhodnius prolixus and reveal that piRNAs, but not the siRNA pathway, responded to HTTs that were recently transferred from vertebrate tetrapods to a hematophagous insect of medical relevance.